The inequality would be 34 > 2 x 3, if I'm correct. I'm not to sure on the graph part though , sorry.
2 Answers:
- B) The lines are parallel
- C) The lines have the same slope.
Parallel lines always have equal slope, but different y intercepts.
==========================================================
Explanation:
Let's solve the second equation for y
3y - x = -7
3y = -7+x
3y = x-7
y = (x-7)/3
y = x/3 - 7/3
y = (1/3)x - 7/3
The equation is in y = mx+b form with m = 1/3 as the slope and b = -7/3 as the y intercept. We see that the first equation, where y was already isolated, also has a slope of m = 1/3. The two equations of this system have the same slope. Choice C is one of the answers.
However, they don't have the same y intercept. The first equation has y intercept b = -4, while the second has b = -7/3. This means that they do not represent the same line. They need to have identical slopes, and identical y intercepts (though the slope can be different from the y intercept of course) in order to have identical lines. So we can rule out choice D and E because of this.
Because the two equations have the same slope, but different y intercepts, this means the lines are parallel. Choice B is the other answer.
Parallel lines never touch or intersect, which in turn means there is no solution point. A solution point is where the lines cross. We can rule out choice A.
I recommend using your graphing calculator, Desmos, GeoGebra, or any graphing tool (on your computer or online) to graph each equation given. You should see two parallel lines forming. I used GeoGebra to make the graph shown below.
<span>The answer is true
Let's imagine that we have the following function function:
</span>
<span>We have to:
Independent variable: x
Dependent variable: y
For x = -1:
</span>
<span> For x = 1:
</span>
<span> We observe that the independent variable can only obtain one result.
Answer:
True</span>
Answer:
87+87+81+86+89+83+89= 602. Divided by 7 because that’s how many numbers there were is 86 and that is your mean/average.
ANSWER
EXPLANATION
We were given that
varies directly as
We can write this mathematically as,
This implies that,
where k is the constant of variation.
This implies that,
The equation becomes
When